Tetraphyllidean metacestodes of teleosts of the Great Barrier Reef, and the use of in vitro cultivation to identify them - Chambers, C B; Cribb, T H; Jones, M K (Folia parasitologica, 2000)
The tetraphyllidean metacestode diversity of 310 teleost fishes, including 87 species from 31 families, was examined from Heron Island, The Great Barrier Reef, Australia. Eleven metacestode 'types' were identified with the use of light microscopy. Host-specificity varied greatly among metacestode types. Incorporation of in vitro cultivation allowed generic identification for some types. Types 1 and 2 belong to Uncibilocularis Southwell, 1925, and have triloculate bothridia and one pair of forked hooks with unequal prongs; Type 3 has quadriloculate bothridia. Hook development was insufficient to determine in which genus, Acanthobothrium van Beneden, 1849 or Calliobothrium van Beneden, 1850, this type may belong. Type 4 has unilocular bothridia with simple edges and belongs to Anthobothrium van Beneden, 1850. Type 5 has multiloculated bothridia which are invaginated within pouches. This type belongs to the Rhinebothriinae although its generic identity cannot be determined. The bothridia of Type 5 everted within 24 hours of in vitro cultivation and revealed the presence of two forms, one having 48 loculi per bothridium, the other 72 per bothridium. In vitro studies provide additional support for existing theories of onchobothriid scolex development.
Keywords: Cestoda; Elasmobranchii; interakce hostitele a parazita; Culture Media; Australia; Animals; Fish Diseases; Microscopy, Electron, Scanning; mikroskopie elektronová rastrovací; cestodózy; Austrálie; zvířata; Cestode Infections; nemoci ryb; Host-Parasite Interactions; kultivační média